EVALUASI IMPLEMENTASI KURIKULUM MATA PELAJARAN PRODUKTIF SMK NEGERI 1 SAMARINDA - Ramli, Akhmad (IKIP PGRI KALIMANTAN TIMUR, 2021)
This study aimed to evaluate the general program implementation curriculum subjects productive trip business skills program in SMK Negeri 1 Samarinda. This study used a qualitative approach. Collecting data using (1) interviews, (2) observations (3) documentation, and (4) Questionnaires. Analysis of data using four components, namely data collection, data reduction, data presentation and conclusion. The results showed (1) The evaluation of the program in the context of components that include requirements analysis, vision, mission, goals and curriculum schools of business expertise trip to the category of